2019
DOI: 10.1016/j.chb.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The Avatar's new clothes: Understanding why players purchase non-functional items in free-to-play games

Abstract: Free-to-play online games create significant revenues through sales of virtual items. The argument that the sale of items that provide a competitive advantage (functional items) fuels a pay-to-win culture has attracted developers to business models that are solely based on the sale of non-functional items (items that provide no objective competitive advantage). However, the motivations for purchasing non-functional items remain under-examined. The present study therefore provides an exploration of hedonic, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 53 publications
4
35
1
38
Order By: Relevance
“…The vast prevalence of such topics supports the previous theoretical and empirical findings (Lehdonvirta 2009;Marder et al 2019), who found that visual representation plays an important role in a player's decision to purchase non-functional items. Not only does the analysis conducted in this work demonstrate that aesthetic value plays a vital role in the evaluation of non-functional items (the range and number of topics associated with aesthetics), but also it shows how the discussion of visual effects reflects increases in the value of the assets.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The vast prevalence of such topics supports the previous theoretical and empirical findings (Lehdonvirta 2009;Marder et al 2019), who found that visual representation plays an important role in a player's decision to purchase non-functional items. Not only does the analysis conducted in this work demonstrate that aesthetic value plays a vital role in the evaluation of non-functional items (the range and number of topics associated with aesthetics), but also it shows how the discussion of visual effects reflects increases in the value of the assets.…”
Section: Discussionsupporting
confidence: 79%
“…Recent work on this topic (Marder et al 2019) supports the findings of Lehdonvirta's work and extends the analysis of emotional and social value in virtual consumption. Analyzing interviews of League of Legends players, the authors extracted nine key themes and found that emotional (hedonic) motivation has five aspects important for players: novelty, aesthetics, reciprocity, self-gratification, and character dedication.…”
Section: Studies Of Communication About Virtual Goods On Redditsupporting
confidence: 64%
See 3 more Smart Citations